Therapeutic Potential of Polyphenols in Cardiac Fibrosis - Zhang, Ning; Wei, Wen-Ying; Li, Ling-Li; Hu, Can; Tang, Qi-Zhu (Frontiers in Pharmacology, 2018)
Cardiac fibrosis, in response to injury and stress, is central to a broad constellation of cardiovascular diseases. Fibrosis decreases myocardial wall compliance due to extracellular matrix accumulation, leading to impaired systolic and diastolic function and causing arrhythmogenesis. Although some conventional drugs, such as β-blockers and renin-angiotensin-aldosterone system (RAAS) inhibitors, have been shown to alleviate cardiac fibrosis in clinical trials, these traditional therapies do not tend to target all the fibrosis-associated mechanisms, and do not hamper the progression of cardiac fibrosis in patients with heart failure. Polyphenols are present in vegetables, fruits and beverages and had been proposed as attenuators of cardiac fibrosis in different models of cardiovascular diseases. Together with results found in the literature, we can show that some polyphenols exert anti-fibrotic and myocardial protective effects by mediating inflammation, oxidative stress and fibrotic molecular signals. This review considers an overview of the mechanisms of cardiac fibrosis, illustrates their involvement in different animal models of cardiac fibrosis treated with some polyphenols and projects the future direction and therapeutic potential of polyphenols on cardiac fibrosis.